P-P48 Clinical Benefit of Surveillance after Resection of Pancreatic Ductal Adenocarcinoma: A Systematic Review and Meta-Analysis. (16th December 2021) - Halle-Smith, James; Hall, Lewis; Daamen, Lois; Hodson, James; Pande, Rupaly; Young, Alastair; Jamieson, Nigel; Lamarca, Angela; van Santvoort, Hjalmar; Molenaar, Izaak Quintus; Valle, Juan; Roberts, Keith
Abstract: Background: The clinical benefit and acceptability to patients of routine surveillance after resection of pancreatic ductal adenocarcinoma (PDAC) remains unclear. Furthermore, expert guidelines around the world offer conflicting recommendations. This study is a systematic review of evidence for surveillance programs. Methods: A systematic review of studies evaluating different surveillance methods was undertaken. Meta-analyses were performed for those studies reporting rates of asymptomatic recurrence, treatment of recurrence and overall survival, according to different surveillance methods. Results: There were ten studies included in the literature review. Five studies were appropriate for meta-analysis (1, 596 patients). If enrolled in an active surveillance program, patients were more likely to have recurrence detected at an asymptomatic stage (Pooled Rate: 49.3% vs. 19.1%, p = 0.043). In terms of clinical outcomes, patients with asymptomatic recurrence were more likely to receive treatment for recurrence (Odds Ratio 3.49; 95% CI: 1.73-7.07; p < 0.001) and had longer overall survival (Mean Difference: 9.5 months; 95% CI: 4.1-14.8; p < 0.001) than those with symptoms at time of recurrence. Conclusions: From this systematic review and meta-analysis of early data it appears that routine surveillance after surgery for PDAC detects more patients at the asymptomatic stage. Data from these non-randomised trials also suggest that treatment rates and survival may be superior in patients were recurrence is detected when asymptomatic. As such, these data suggest that routine surveillance may improve patient outcomes, however an appropriately conducted trial would be required to address concerns that various sources of bias may be affecting these results.